Licence to operate: Social Return on Investment as a multidimensional discursive means of legitimating organisational action. Issue 3 (7th November 2016) - Klemelä, Juha
Abstract : Purpose: The Social Return on Investment (SROI) framework has for mapping and measuring social impact. It may be used for legitimating organisations and projects. The framework is often criticised for its overemphasis of the SROI ratio, i.e. the relationship between monetised benefits and costs. This study aims to demonstrate how the SROI method legitimates organisations or projects with multiple other discursive ways besides the SROI ratio. It also discusses the status of these other ways of legitimation in relation to the quantifying and monetising core tendency of SROI. Design/methodology/approach: The empirical data consist of an SROI guidebook and 12 SROI reports. Their study applies Theo van Leeuwen's ideas for analysing the discursive legitimation of social practices. The study takes place broadly in the framework of Norman Fairclough's critical discourse analysis, aided by qualitative content analysis. Findings: In the analysis, the full spectrum of the van Leeuwenian legitimation means used by SROI – authorisation, rationalisation, moral evaluation and mythopoetical narration – is brought out in the data and the status and social context of the legitimation means are assessed and discussed. It is shown that there is existing potential for broader and more visible use of different legitimation means. Practical implications: Based on the findings of the study, suggestions for the improvement of SROI reporting by a more balanced explicit use of the multitude of legitimation means are presented. Originality/value: The study is original both in its subject (the spectrum of legitimation in SROI) and its method (qualitative discursive and contentual analysis of SROI as a legitimating discourse).